Association between socioeconomic status and risk of hospitalization due to child maltreatment in the USA. (3rd October 2018) - Imran, Sehyr; Cross, Chad; Das, Samrat U
Abstract : Child maltreatment remains a significant problem in the USA. There is a dearth of literature examining the association of socioeconomic status (SES) and incidence of child maltreatment among hospitalized children across the entire USA. Our aim was to study the association between SES and incidence and mortality from child maltreatment among hospitalized children in the USA. We used 2013–2014 data from the Nationwide Inpatient Sample, a discharge database representative of all hospitals in the USA. International Classification of Diseases-9 codes for general child maltreatment were used to identify patients discharged with a primary diagnosis of child maltreatment. Trends in the incidence and outcomes of child maltreatment were compared with SES based on quartiles (Qx) of median household income. In 2013–2014, there were a total of about 2.3 million pediatric discharges. Out of these, a total of 8985 had a primary diagnosis of child maltreatment. Approximately 40 per cent of the cases were from families with the lowest SES (Q1). In-hospital mortality was 2.4 per cent in Q1 (lowest SES) compared with 0.4 per cent in Q4 (highest SES). We conclude that children from lower SES households have a higher incidence of child maltreatment and have worse outcomes, including significantly higher in-hospital mortality among hospitalized children. This trend was generally consistent across all age groups and ethnicities. To our knowledge, this is the first report studying the association between SES and children with child maltreatment among hospitalized children across the entire USA.